Kinetics and thermodynamics of acoustic release of doxorubicin from non-stabilized polymeric micelles - Husseini, Ghaleb (2010)
This paper studies the thermodynamic characteristics of ultrasound-activated release of Doxorubicin (Dox) from micelles. The release and re-encapsulation of Dox into Pluronic® P105 micelles was measured by recording the fluorescence of a solution of 10 μg/ml Dox and 10 wt% P105 polymer in phosphate-buffered saline, during and after insonation by ultrasound at three temperatures (25 °C, 37 °C and 56 °C). The experimental data were modeled using a previously published model of the kinetics of the system. The model was simplified by the experimental measurement of one of the parameters, the maximum amount of Dox that can be loaded into the poly(propyleneoxide) cores of the micelles, which was found to be 89 mg/ml PPO and 150 mg Dox/ml PPO at 25 °C and 37 °C, respectively. From the kinetic constants and drug distribution parameters, we deduced the thermodynamic activation energy for micelle re-assembly and the residual activation energies for micelle destruction. Our model showed that the residual activation energy for destruction decreased with increasing acoustic intensity. In addition, higher temperatures were found to encourage micelle destruction and hinder micelle re-assembly.